THE POTENTIAL PROSPECT OF ARTIFICIAL INTELLIGENCE (AI) IN ARBITRATION FROM THE INTERNATIONAL, NATIONAL AND ISLAMIC PERSPECTIVES (Journal of International Studies, 2023)
Arbitration is the most widespread mechanism for resolving disputes in the modern and Islamic eras. The current global tendency calls for an increase in the integration of disruptive technology, such as artificial intelligence (AI), into arbitration. Using doctrinal legal research methodology, this article examines the potential prospect of artificial intelligence (AI) in arbitration from international, national, and Islamic perspectives. To achieve that, several international arbitration laws, such as the Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958 and UNCITRAL Model Law on International Commercial Arbitration 1985, national arbitration laws, such as Arbitration Act 2005 (Act 646), UK Arbitration Act 1996, and Singaporean Arbitration Act 2011, and the Islamic law were analysed. The collected data was analytically and critically analysed using the content analysis method. It is found that AI technologies would bring added value to arbitration if they are appropriately employed. However, from a legal perspective, arbitration laws are not mature enough to absorb AI technologies. Besides, it has been discovered that Islam does not prohibit AI technologies as long as they can serve humanity. According to the Islamic point of view, an artificial intelligence arbitrator (AIA) cannot replace human arbitrators. Finally, this article provides several recommendations to enhance the use of AI technologies and AIA in arbitration. This, in turn, would help in creating a modern, prosperous, and just world and improving the international relations between nations, international organisations, and individuals from different countries as any of them could resolve their disputes effectively.